Comparison of Several Types of Plasma as Media in the Germ Tube Test for Identification of Candida albicans - Hidayati, Yunia; Asnaily, Asnaily; Jumaisal, Akhirul; Simanjuntak, James Perdinan (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Candida albicans is a commensal on the oral mucosal surfaces of healthy individuals but can be pathogenic in immunocompromised individuals. The germ tube test is an inexpensive, faster, and easier method used to identify and differentiate it from other yeast species. Generally, the test is carried out using serum as the medium. Plasma overall has the same characteristics as serum and differs only in the content of clotting factors. In addition, plasma is easier to obtain than serum in most healthcare services. This study aims to demonstrate three types of plasma as alternative media for germ tube tests. CPDA (Citrate Phosphate Dextrose Adenine), EDTA (Ethylenediaminetetraacetic), and Sodium Citrate plasma were compared to serum in producing of germ tubes. Each plasma and serum was tested in five repetitions. The experimental method was carried out in Mycology Laboratory at the Health Polytechnic of Jambi. The data were observed based on the germ tube formation time and analyzed with a one-way ANOVA test. The average germ tube formation times observed in this study were 70 minutes (serum), 129 minutes (CPDA plasma), 164 minutes (EDTA plasma), and 146 minutes (Citrate plasma). The lengths were significantly different between serum and the three plasma (P>0.05). Nevertheless, CPDA plasma showed the average time which is at the minimum incubation time limit according to the standard protocol of the test. The CPDA plasma was faster than other plasma in the formating time of the germination. Therefore, CPDA plasma can be recommended as a substitute for serum in the germ tube test for it was easier to obtain, and considered safer to use.